Sphingolipid metabolism and cell signaling. - Merrill, Alfred H. (Alfred Harrison), 1951-; Hannun, Yusuf A., 1955- (Methods in enzymology, 2000)
This volume contains information on analyzing sphingolipids, sphingolipid transport and trafficking, and sphingolipid-protein interactions and cellular targets. Its companion Volume 311 presents methods used in studying enzymes of sphingolipid biosynthesis and turnover, including inhibitors of some of these enzymes, genetic approaches, and organic and enzymatic syntheses of sphingolipids and analogs. The critically acclaimed laboratory standard for more than forty years, Methods in Enzymology is one of the most highly respected publications in the field of biochemistry. Since 1955, each volume.